P (AM (at) AA)-CuFe material and preparation method and application thereof
By grafting and modification on CuHCF nanoparticles, P(AM@AA)-CuFe material is formed, which solves the problems of low effective utilization rate and high preparation cost caused by agglomeration and stacking of CuHCF nanoparticles, and achieves efficient adsorption and reuse of cesium ions.
Patent Information
- Application Number
- CN202510037484.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-01-09
AI Technical Summary
In the prior art, CuHCF nanoparticles are prone to agglomeration and stacking, resulting in low effective utilization, high production cost, strict working environment conditions, and difficult to effectively adsorb and separate high-thermorenolic nuclides such as 137Cs.
Porous hydrophilic polymers were prepared by water-in-water emulsion template technology, and CuFe nanoparticles were grafted onto the polymer through coordination bonds to form P(AM@AA)-CuFe material. The material has a porous mesh structure and high porosity, and the CuFe nanoparticles are evenly distributed, improving adsorption performance.
Highly efficient adsorption of cesium ions in water is achieved, with a maximum adsorption capacity of 175 mg/g, an adsorption equilibrium time within 100 min, and high selectivity and reuse performance are shown in the presence of multiple ions.
Smart Images

Figure CN119751968A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nanomaterials, and in particular to a P(AM@AA)-CuFe material and a preparation method and application thereof. Background Art
[0002] The spent fuel reprocessing process in the nuclear industry chain will produce a large amount of high-level waste liquid. 137 As a high-heat-releasing nuclide in waste liquid, Cs is easily absorbed by plants and animals once it leaks into the environment, thus damaging the ecological environment and threatening human health. 137 Cs can also be made into heat-releasing elements, radiation sources, catalysts, etc. 137 It is of great significance to separate and extract Cs from high-level radioactive waste or nuclear contaminated water. In the prior art, metal organic frameworks (MOFs) have the advantages of large specific surface area, adjustable pores, and functional modification, and are often used for the separation of metal ions. Among them, CuHCF, as a Prussian blue analog (PBA), is a typical MOF material that can selectively adsorb cesium ions. However, on the one hand, CuHCF nanoparticles are very easy to agglomerate and stack, resulting in low effective utilization rate. On the other hand, there are also problems such as high preparation cost and harsh working environment conditions. Summary of the invention
[0003] The object of the present invention is to provide a P(AM@AA)-CuFe material with stable adsorption performance and good adsorption effect, and a preparation method and use thereof.
[0004] The present invention provides a P(AM@AA)-CuFe material, comprising a hydrophilic polymer with a porous network structure and CuFe nanoparticles uniformly distributed on the surface of the hydrophilic polymer, wherein the CuFe nanoparticles are agglomerated stacks with a size range of 100-200 nm, and the CuFe nanoparticles are grafted onto the hydrophilic polymer through coordination bonds.
[0005] Furthermore, the CuFe nanoparticles of the P(AM@AA)-CuFe material of the present invention are grafted using the active functional groups -OH and -NH2 on the polymer as anchor points, and the grafting rate of the CuFe nanoparticles in the P(AM@AA)-CuFe material is 57% to 61%. The grafting rate refers to the mass ratio of the CuFe nanoparticles in the composite material.
[0006] Furthermore, the porosity of the P(AM@AA)-CuFe material of the present invention is ≥70%. Porosity refers to the ratio of the pore volume inside the material to the total volume of the material, usually expressed as a percentage.
[0007] On the other hand, the present invention provides a method for preparing the P(AM@AA)-CuFe material based on any of the above-mentioned materials, wherein the method firstly adopts a water-in-water emulsion template technology to prepare a porous hydrophilic polymer, and then uses the active functional groups -OH and -NH2 on the porous hydrophilic polymer as anchors to in-situ grow and fix CuFe nanoparticles thereon, thereby preparing the P(AM@AA)-CuFe material; The preparation method specifically comprises the following steps: 1) dissolving appropriate amounts of glucan and cellulose nanocrystals in water as solution A, wherein the mass concentration of glucan in solution A is 0.1-0.2 g / mL, and the mass concentration of cellulose nanocrystals is 0.02-0.03 g / mL; 2) dissolving an appropriate amount of PEG and MBAM in water as solution B, wherein the mass concentration of PEG in solution B is 0.2-0.25 g / mL, and the mass concentration of MBAM is 0.1-0.15 g / mL; 3) Add appropriate amount of AM and AA to solution B to prepare PEG / AM-AA solution; the volume ratio of AM:AA:solution B is (1-4):(1-4):1; 4) mixing the PEG / AM-AA solution and solution A in a volume ratio of (1-2):(4-5), placing the mixture in an ice water bath, and stirring the mixture to obtain a mixed solution; 5) adding an appropriate amount of initiator to the mixed solution to obtain a sol mixture, transferring the sol mixture into a mold, and placing it in a water bath for reaction for 8-12 hours to obtain an intermediate product P(AM@AA); the initiator includes KPS and TMEDA, and the volume ratio of KPS:TMEDA:mixed solution is (1-2):(1-2):(25-30); 6) The intermediate product P(AM@AA) is immersed in a 0.1~0.4 M CuCl2 solution for 6~12 h, and then immersed in a 0.05~0.2 M K4Fe(CN)6 solution for 6~12 h, and then the obtained product is placed in ultrapure water for standing and washing for 12~36 h to obtain the P(AM@AA)-CuFe material.
[0008] In the present application, AM is acrylamide; AA is acrylic acid; PEG is polyethylene glycol; MBAM is methylenebisacrylamide; KPS is potassium persulfate, and TMEDA is N,N,N',N'-tetramethylethylenediamine. In addition, the AA content in the preparation method must be appropriate. If the amount of AA added is too little, the adsorption capacity of the prepared P(AM@AA)-CuFe material is low; on the contrary, if the amount of AA added is too much, the P(AM@AA)-CuFe material will easily absorb water, swell and rupture, and the mechanical properties will be poor.
[0009] Furthermore, in step 5) of the preparation method of the present invention, the temperature of the water bath is 40°C to 50°C.
[0010] Furthermore, the cellulose nanocrystals prepared by the method of the present invention are rod-shaped cellulose with a length of 100-200 nm and a diameter of 8-10 nm.
[0011] Furthermore, in step 4) of the preparation method of the present invention, the temperature of the ice water bath is -2 to 5°C, and in step 4) mechanical stirring and mixing are performed at a stirring rate of 250 to 350 rpm to ensure uniform mixing.
[0012] Furthermore, the mold in step 5) of the preparation method of the present invention is a cubic silicone mold with a side length of 10 mm.
[0013] In addition, the present invention also provides a use of any of the above-mentioned P(AM@AA)-CuFe materials, wherein the P(AM@AA)-CuFe material is used to adsorb cesium ions in water.
[0014] Furthermore, in the use described in the present invention, the maximum adsorption capacity of the P(AM@AA)-CuFe material for cesium ions is 175 mg / g, the time to reach adsorption equilibrium is t, and it satisfies 100 min≤t≤120 min.
[0015] Furthermore, in the use described in the present invention, the adsorption rate of the P(AM@AA)-CuFe material for cesium ions in the solution is greater than 85%, wherein the pH of the solution is 2-8, and the solution includes one or more of strontium ions, nickel ions, aluminum ions, sodium ions, potassium ions, calcium ions, magnesium ions, and ions of lanthanide elements.
[0016] Furthermore, in the use described in the present invention, the adsorption rate of the P(AM@AA)-CuFe material for cesium ions in the solution is greater than 90%, wherein the pH of the solution is 3-8, and the solution includes one or more of strontium ions, nickel ions, aluminum ions, sodium ions, potassium ions, calcium ions, magnesium ions, and ions of lanthanide elements.
[0017] Furthermore, in the use described in the present invention, after continuous adsorption-desorption of the P(AM@AA)-CuFe material, the adsorption rate of cesium ions at the fourth adsorption is greater than 80%.
[0018] Compared with the prior art, the present invention has the following beneficial technical effects: The P(AM@AA)-CuFe material of the present invention has a porosity of ≥70%, and includes a hydrophilic polymer with a porous network structure, and CuFe nanoparticles uniformly distributed on the surface of the hydrophilic polymer, wherein the CuFe nanoparticles are agglomerated stacks with a size range of 100-200 nm, and the CuFe nanoparticles are grafted onto the hydrophilic polymer through coordination bonds. The CuFe nanoparticles are grafted using active functional groups -OH and -NH2 on the polymer as anchor points, and the grafting rate of the CuFe nanoparticles in the P(AM@AA)-CuFe material is 57%-61%.
[0019] The preparation method of the present invention adopts water-in-water (w / w) emulsion template technology to prepare porous hydrophilic polymers. No large amount of organic solvents are required in the production process, thus overcoming the problem of solvent residues in the final product, having no significant impact on the environment and having low cost.
[0020] The P(AM@AA)-CuFe material of the present invention can transfer Cs + accommodated, and there is also K in the material + With Cs + ion exchange, thereby adsorbing cesium ions in water. Moreover, it has the characteristics of high selectivity, high adsorption capacity and rapid adsorption equilibrium when adsorbing cesium ions. The adsorption capacity of cesium ions at 25°C can reach up to 175 mg / g, and the adsorption equilibrium can be reached in 100 min. The adsorption rate of cesium ions in the solution of the P(AM@AA)-CuFe material is greater than 85%, wherein the pH of the solution is 2-8, and the solution includes strontium ions, nickel ions, aluminum ions, sodium ions, potassium ions, calcium ions, magnesium ions, and one or more ions of lanthanide elements. After continuous adsorption-desorption of the P(AM@AA)-CuFe material, the adsorption rate of cesium ions for the fourth adsorption is greater than 80%. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a microscopic morphology of the P(AM@AA)-CuFe material of the present invention; Figure 2 This is an enlarged microscopic morphology of the P(AM@AA)-CuFe material of the present invention; Figure 3 This is the element distribution diagram of the P(AM@AA)-CuFe material of the present invention; Figure 4 This is the element distribution diagram of the P(AM@AA)-CuFe material of the present invention after adsorbing cesium ions; Figure 5This is an analysis of the adsorption of Cs ions by P(AM@AA)-CuFe materials at different initial concentrations in Examples 2 and 11 to 13 of the present invention; Figure 6 Analysis of the adsorption process of Cs ions on P(AM@AA)-CuFe material with respect to time; Figure 7 To analyze the effect of different metal ions on the adsorption of Cs ions by P(AM@AA)-CuFe materials; Figure 8 The recyclability of the P(AM@AA)-CuFe material of the present invention; Fig. 9 The adsorption rate and XRD of the P(AM@AA)-CuFe material at different pH values in Examples 2, 5 to 10 and Comparative Example 3 of the present invention; Fig.10 This is a state diagram of the P(AM@AA)-CuFe material after absorbing water in Example 14, Example 15, Comparative Example 1 and Comparative Example 2 of the present invention; Fig.11 This is an analysis of the results of cesium ion adsorption by the P(AM@AA)-CuFe material described in Example 14, Example 15 and Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0022] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described in detail with reference to the accompanying drawings. The described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the specific implementation methods, they shall be carried out according to the conventional conditions or the conditions recommended by the manufacturer.
[0023] When the following description refers to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present disclosure. Instead, they are merely examples of devices and methods consistent with some aspects of the present disclosure as detailed in the appended claims. The terms used in the present disclosure are only for the purpose of describing specific embodiments and are not intended to limit the present disclosure.
[0024] The present invention is further described in detail below in conjunction with specific embodiments. Specific implementation method 1
[0025] A P(AM@AA)-CuFe material comprises a hydrophilic polymer with a porous network structure and CuFe nanoparticles uniformly distributed on the surface of the hydrophilic polymer, wherein the CuFe nanoparticles are agglomerated stacks with a size range of 100-200 nm, and the CuFe nanoparticles are grafted onto the hydrophilic polymer through coordination bonds.
[0026] In other specific embodiments, the CuFe nanoparticles of the P(AM@AA)-CuFe material are grafted using the active functional groups -OH and -NH2 on the polymer as anchor points, and the grafting rate of the CuFe nanoparticles in the P(AM@AA)-CuFe material is 57% to 61%. The grafting rate refers to the mass ratio of the CuFe nanoparticles in the composite material.
[0027] In other specific embodiments, the porosity of the P(AM@AA)-CuFe material is ≥70%. Porosity refers to the ratio of the pore volume inside the material to the total volume of the material, usually expressed as a percentage. Specific implementation method 2
[0028] A method for preparing a P(AM@AA)-CuFe material based on any of the above embodiments, wherein the method firstly prepares a porous hydrophilic polymer using a water-in-water emulsion template technology, and then uses the active functional groups -OH and -NH2 on the porous hydrophilic polymer as anchors to in-situ grow and fix CuFe nanoparticles thereon, thereby preparing a P(AM@AA)-CuFe material; The preparation method specifically comprises the following steps: 1) dissolving appropriate amounts of glucan and cellulose nanocrystals in water as solution A, wherein the mass concentration of glucan in solution A is 0.1-0.2 g / mL, and the mass concentration of cellulose nanocrystals is 0.02-0.03 g / mL; 2) dissolving an appropriate amount of PEG and MBAM in water as solution B, wherein the mass concentration of PEG in solution B is 0.2-0.25 g / mL, and the mass concentration of MBAM is 0.1-0.15 g / mL; 3) Add appropriate amount of AM and AA to solution B to prepare PEG / AM-AA solution; the volume ratio of AM:AA:solution B is (1-4):(1-4):1; 4) mixing the PEG / AM-AA solution and solution A in a volume ratio of (1-2):(4-5), placing the mixture in an ice water bath, and stirring the mixture to obtain a mixed solution; 5) adding an appropriate amount of initiator to the mixed solution to obtain a sol mixture, transferring the sol mixture into a mold, and placing it in a water bath for reaction for 8-12 hours to obtain an intermediate product P(AM@AA); the initiator includes KPS and TMEDA, and the volume ratio of KPS:TMEDA:mixed solution is (1-2):(1-2):(25-30); 6) The intermediate product P(AM@AA) is immersed in a 0.1~0.4 M CuCl2 solution for 6~12 h, and then immersed in a 0.05~0.2 M K4Fe(CN)6 solution for 6~12 h, and then the obtained product is placed in ultrapure water for standing and washing for 12~36 h to obtain the P(AM@AA)-CuFe material.
[0029] In other specific embodiments, the temperature of the water bath in step 5) of the preparation method is 40°C to 50°C.
[0030] In other specific embodiments, the cellulose nanocrystals prepared by the method are rod-shaped cellulose with a length of 100-200 nm and a diameter of 8-10 nm.
[0031] In other specific embodiments, in step 4) of the preparation method, the temperature of the ice water bath is -2-5°C, and in step 4), mechanical stirring and mixing are performed at a stirring rate of 250-350 rpm to ensure uniform mixing.
[0032] In other specific embodiments, the mold in step 5) of the preparation method is a cubic silicone mold with a side length of 10 mm. Specific implementation method three
[0033] A use of the P(AM@AA)-CuFe material based on any of the above specific embodiments, wherein the P(AM@AA)-CuFe material is used to adsorb cesium ions in water.
[0034] In other specific embodiments, the maximum adsorption capacity of the P(AM@AA)-CuFe material for cesium ions is 175 mg / g, the time to reach adsorption equilibrium is t, and 100 min≤t≤120 min is satisfied.
[0035] In other specific embodiments, the adsorption rate of the P(AM@AA)-CuFe material for cesium ions in the solution is greater than 85%, wherein the pH of the solution is 2-8, and the solution includes one or more of strontium ions, nickel ions, aluminum ions, sodium ions, potassium ions, calcium ions, magnesium ions, and ions of lanthanide elements.
[0036] In other specific embodiments, after continuous adsorption-desorption of the P(AM@AA)-CuFe material, the adsorption rate of cesium ions at the fourth adsorption is greater than 80%. Example 1
[0037] 1-4 g of dextran and 0.5-1 g of cellulose nanocrystals were weighed and dissolved in 17-20 mL of water as solution A, and 0.5-1 g of PEG and 0.5-1 g of MBAM were weighed and dissolved in 5-10 mL of water as solution B. In addition, AM and AA were added to solution B to prepare PEG / AM-AA solution, wherein the volume ratio of AM:AA:solution B was (1-4):(1-4):1. Subsequently, the above PEG / AM-AA solution and solution A were placed in an ice water bath and mechanically stirred at a stirring rate of 300 rpm to mix evenly. Then, initiators KPS and TMEDA were added to the mixed solution, and the sol-gelled mixture was immediately transferred into a mold and placed in a 45°C water bath for reaction for 12 h to obtain the intermediate product P(AM@AA). The volume ratio of KPS added:TMEDA:mixed solution was (1-2):(1-2):(25-30). The intermediate product P(AM@AA) was immersed in a 0.1~0.4 M CuCl2 solution for 6~12 h, and then immersed in a 0.05~0.2 M K4Fe(CN)6 solution for 6~12 h, and then CuFe nanoparticles were grown in the intermediate product P(AM@AA). After the reaction was completed, the product was placed in ultrapure water and washed for 12 h to obtain the composite material P(AM@AA)-CuFe.
[0038] like Figure 1~Figure 3 As shown, the P(AM@AA)-CuFe material has a hydrophilic polymer with a porous network structure, and CuFe nanoparticles uniformly distributed on the surface of the hydrophilic polymer. The CuFe nanoparticles are agglomerated stacks with a size range of 100-200 nm, and the CuFe nanoparticles are grafted onto the hydrophilic polymer through coordination bonds. And according to the test, the grafting rate of the CuFe nanoparticles in the P(AM@AA)-CuFe material is 57%-61%. The porosity of the P(AM@AA)-CuFe material is 70.69%. Example 2
[0039] 6-20 mg of the P(AM@AA)-CuFe material obtained in Example 1 was added to 8 mL of a CsNO3 solution with a concentration of 60-600 ppm and a pH of 7, and the mixture was shaken at 200 rpm in a shaker at a temperature of 25°C. After continuous shaking, the mixture was filtered using a 0.22 μm syringe filter membrane. The filtrate was used to measure the concentration of Cs ions using an inductively coupled plasma optical emission spectrometer (ICP-OES). The adsorption amount (q e , mg / g) and adsorption rate (RE, %) to evaluate the performance of the adsorbent: (1) (2) Where c0 (mgL −1 ) and c e (mgL −1 ) are the initial concentration and equilibrium concentration of Cs ions, respectively. V (L) is the volume of the solution, m (g).
[0040] It was calculated that the adsorption capacity of P(AM@AA)-CuFe material for Cs(Ⅰ) can reach up to 175 mg / g at 25°C, and the adsorption equilibrium can be reached in 100 min. Figure 5 and Figure 6 As shown. Figure 5 As shown in the figure, the adsorption rate of cesium ions by P(AM@AA)-CuFe material is 46~99%. Analysis of P(AM@AA)-CuFe material after adsorption of cesium ions shows that the adsorption process transfers Cs + accommodated, and there is also K in the material + With Cs + Ion exchange, such as Figure 4 shown. Example 3
[0041] The difference between Example 3 and Example 2 is that the CsNO3 solution also includes strontium ions, nickel ions, aluminum ions, sodium ions, potassium ions, calcium ions, magnesium ions, as well as La ions, Eu ions and Lu ions. Figure 7 As shown in the figure, the adsorption rate of P(AM@AA)-CuFe material for cesium ions is also 90-95%. It can be seen that whether in a system where multiple metal ions with different valence states coexist or in seawater, P(AM@AA)-CuFe material shows super strong selectivity for Cs ions. Example 4
[0042] The P(AM@AA)-CuFe material after adsorbing cesium ions in Example 3 was placed in a 0.5-1 M KCl solution for elution, and shaken in a shaker at 25°C for 2-6 h to obtain the resolved material, which was directly removed and re-added with the original solution of Cs ions for a new round of adsorption. After three cycles of use, the fourth adsorption rate can still reach more than 80%, as shown in FIG. Figure 8 As shown, the P(AM@AA)-CuFe material exhibits good recycling performance. Example 5
[0043] The difference between Example 5 and Example 2 is that the pH is 2, and the adsorption rate of cesium ions by the P(AM@AA)-CuFe material is 86%. Example 6
[0044] The difference between Example 6 and Example 2 is that the pH is 3, and the adsorption rate of cesium ions by the P(AM@AA)-CuFe material is 91%. Example 7
[0045] The difference between Example 7 and Example 2 is that the pH is 4, and the adsorption rate of cesium ions by the P(AM@AA)-CuFe material is 90.5%. Example 8
[0046] The difference between Example 8 and Example 2 is that the pH is 5, and the adsorption rate of cesium ions by the P(AM@AA)-CuFe material is 92.5%. Example 9
[0047] The difference between Example 9 and Example 2 is that the pH is 6, and the adsorption rate of cesium ions by the P(AM@AA)-CuFe material is 93%.
[0048] Embodiment 10: The difference between Example 10 and Example 2 is that the pH is 8, and the adsorption rate of cesium ions by the P(AM@AA)-CuFe material is 91%.
[0049] Embodiment 11: The difference between this embodiment 11 and embodiment 2 is only that: the concentration of cesium ions in the CsNO3 solution is 700 ppm, and the adsorption capacity of the P(AM@AA)-CuFe material for Cs ions at 25°C can reach up to 165.3 mg / g, and the adsorption equilibrium can be reached in 100 min, and the adsorption rate of the P(AM@AA)-CuFe material for cesium ions is 34%.
[0050] Embodiment 12: The difference between this Example 12 and Example 2 is only that: the concentration of cesium ions in the CsNO3 solution is 800 ppm, and the adsorption capacity of the P(AM@AA)-CuFe material for Cs ions at 25°C can reach up to 163 mg / g, and the adsorption equilibrium can be reached in 100 min, and the adsorption rate of the P(AM@AA)-CuFe material for cesium ions is 28%.
[0051] Embodiment 13: The difference between this Example 13 and Example 2 is only that: the concentration of cesium ions in the CsNO3 solution is 900 ppm, and the adsorption capacity of the P(AM@AA)-CuFe material for Cs ions at 25°C can reach up to 164 mg / g, and the adsorption equilibrium can be reached in 100 min, and the adsorption rate of the P(AM@AA)-CuFe material for cesium ions is 26%.
[0052] Embodiment 14: The difference between Example 14 and Example 1 is that the volume ratio of AA to solution B is 3:1, and finally 3#P(AM@AA)-CuFe material is obtained. The 3#P(AM@AA)-CuFe material is subjected to the adsorption process of Example 2, and finally the adsorption rate of cesium ions of 3#P(AM@AA)-CuFe material is measured to be 52.5%, and the adsorption capacity is 105.9 mg / g. The results are as follows Fig.11 shown.
[0053] Embodiment 15: The difference between Example 15 and Example 1 is that the volume ratio of AA to solution B is 1:1. Finally, 2#P(AM@AA)-CuFe material is obtained. The 2#P(AM@AA)-CuFe material is subjected to the adsorption process of Example 2, and the adsorption rate of cesium ions of the 2#P(AM@AA)-CuFe material is finally measured to be 47.6%, and the adsorption capacity is 96 mg / g. The results are as follows Fig.11 shown.
[0054] Comparative Example 1: The difference between this comparative example 1 and example 1 is that the volume ratio of AA to solution B is 0.5:1. Finally, 1#P(AM@AA)-CuFe material is obtained. The 1#P(AM@AA)-CuFe material is subjected to the adsorption process of example 2, and finally the adsorption rate of cesium ions of the 1#P(AM@AA)-CuFe material is measured to be 31.6%, and the adsorption capacity is 63.66 mg / g. The results are as follows Fig.11 shown.
[0055] Comparative Example 2: The difference between this comparative example 2 and example 1 is that the volume ratio of AA to solution B is 5:1. Finally, the 4#P(AM@AA)-CuFe material is obtained. The 4#P(AM@AA)-CuFe material is subjected to the adsorption process of example 2, and it is found that the 4#P(AM@AA)-CuFe material swells and ruptures after absorbing water, as shown in FIG. Fig.10 shown.
[0056] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that the pH is 1 and the adsorption rate of cesium ions by the P(AM@AA)-CuFe material is 60%.
[0057] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that the pH is 9. At this time, the pH is too high, the CuFe nanoparticles will decompose, and the adsorption effect is poor.
[0058] The present invention is described by the above-mentioned specific embodiments, and it should be understood by those skilled in the art that various changes and equivalent substitutions may be made to the present invention without departing from the scope of the present invention. The parts not described in detail in the present specification are known to those skilled in the art. In addition, various modifications may be made to the present invention for specific situations or specific circumstances without departing from the scope of the present invention. Therefore, the present invention is not limited to the disclosed specific embodiments, but should include all implementation modes falling within the scope of the claims of the present invention.
Claims
1. A P(AM@AA)-CuFe material, characterized in that: The P(AM@AA)-CuFe material includes a hydrophilic polymer with a porous network structure and CuFe nanoparticles uniformly distributed on the surface of the hydrophilic polymer. The CuFe nanoparticles are agglomerated stacks with a size range of 100 to 200 nm, and the CuFe nanoparticles are grafted onto the hydrophilic polymer through coordination bonds.
2. The P(AM@AA)-CuFe material according to claim 1, characterized in that: The CuFe nanoparticles are grafted using active functional groups -OH and -NH2 on the polymer as anchor points, and the grafting rate of the CuFe nanoparticles in the P(AM@AA)-CuFe material is 57% to 61%.
3. The P(AM@AA)-CuFe material according to claim 1, characterized in that: The porosity of the P(AM@AA)-CuFe material is ≥70%.
4. A method for preparing the P(AM@AA)-CuFe material according to any one of claims 1 to 3, characterized in that: The preparation method firstly adopts water-in-water emulsion template technology to prepare a porous hydrophilic polymer, and then uses the active functional groups -OH and -NH2 on the porous hydrophilic polymer as anchor points to in-situ grow and fix CuFe nanoparticles on the hydrophilic polymer, thereby preparing P(AM@AA)-CuFe material; The preparation method specifically comprises the following steps: 1) dissolving appropriate amounts of glucan and cellulose nanocrystals in water as solution A, wherein the mass concentration of glucan in solution A is 0.1-0.2 g / mL, and the mass concentration of cellulose nanocrystals is 0.02-0.03 g / mL; 2) dissolving an appropriate amount of PEG and MBAM in water as solution B, wherein the mass concentration of PEG in solution B is 0.2-0.25 g / mL, and the mass concentration of MBAM is 0.1-0.15 g / mL; 3) Add appropriate amount of AM and AA to solution B to prepare PEG / AM-AA solution; the volume ratio of AM:AA:solution B is (1-4):(1-4):1; 4) mixing the PEG / AM-AA solution and solution A in a volume ratio of (1-2):(4-5), placing the mixture in an ice water bath, and stirring the mixture to obtain a mixed solution; 5) adding an appropriate amount of initiator to the mixed solution to obtain a sol mixture, transferring the sol mixture into a mold, and placing it in a water bath for reaction for 8-12 hours to obtain an intermediate product P(AM@AA); the initiator includes KPS and TMEDA, and the volume ratio of KPS:TMEDA:mixed solution is (1-2):(1-2):(25-30); 6) Soaking the intermediate product P(AM@AA) in a 0.1~0.4 M CuCl2 solution for 6~12 h, and then soaking it in a 0.05~0.2 M K4Fe(CN)6 solution for 6~12 h, and then placing the obtained product in ultrapure water for standing and washing for 12~36 h to obtain the P(AM@AA)-CuFe material.
5. The preparation method according to claim 3, characterized in that: The temperature of the water bath in step 5) is 40°C to 50°C.
6. The preparation method according to claim 4, characterized in that: Cellulose nanocrystals are rod-shaped cellulose with a length of 100~200nm and a diameter of 8~10nm.
7. A use of a P(AM@AA)-CuFe material, characterized in that: The P(AM@AA)-CuFe material is the P(AM@AA)-CuFe material according to any one of claims 1 to 3 or the P(AM@AA)-CuFe material prepared by the preparation method of the P(AM@AA)-CuFe material according to any one of claims 4 to 5, and the P(AM@AA)-CuFe material is used to adsorb cesium ions in water.
8. The use according to claim 7, characterized in that The maximum adsorption capacity of the P(AM@AA)-CuFe material for cesium ions is 175 mg / g, the time to reach adsorption equilibrium is t, and it satisfies 100 min≤t≤120 min.
9. The use according to claim 8, characterized in that The adsorption rate of the P(AM@AA)-CuFe material for cesium ions in the solution is greater than 85%, the pH of the solution is 2-8, and the solution includes one or more of strontium ions, nickel ions, aluminum ions, sodium ions, potassium ions, calcium ions, magnesium ions, and ions of lanthanide elements.
10. The use according to claim 9, characterized in that After three consecutive adsorption-desorptions of the P(AM@AA)-CuFe material, the adsorption rate of cesium ions in the fourth adsorption is greater than 80%.
Citation Information
Patent Citations
Preparation method of particulate cesium removal inorganic ion adsorbent, and product and application of adsorbent
CN105944658A
Mesoporous silica gel loaded with nanoparticles of Prussian blue and analogues thereof, and preparation and application thereof
CN108160040A
Preparation method of cesium-strontium adsorbent particles
CN111589411A
Preparation method of porous material
CN113024733A
Cesium adsorbent and method of preparing the same
US20200061577A1